2010
DOI: 10.3109/09513590.2010.501888
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of melatonin on the precocious puberty: a pilot study

Abstract: Despite the sleep data, melatonin may be involved in the precocious puberty process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Melatonin plays a pivotal role in female reproduction, including puberty, ovarian follicle growth, ovulation, and luteinization [ 29 , 30 , 31 ]. Several studies have demonstrated that melatonin has beneficial effects on oocyte maturation and subsequent embryo development in many species, such as mice [ 32 ], cattle [ 33 ], and pigs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin plays a pivotal role in female reproduction, including puberty, ovarian follicle growth, ovulation, and luteinization [ 29 , 30 , 31 ]. Several studies have demonstrated that melatonin has beneficial effects on oocyte maturation and subsequent embryo development in many species, such as mice [ 32 ], cattle [ 33 ], and pigs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, melatonin secretion has been associated with reproductive development and the timing of human puberty in some studies [14][16]. However aspects of this work has methodological flaws [14], [15] and other studies have failed to replicate the finding [17], [18].…”
Section: Introductionmentioning
confidence: 90%
“…A number of animal studies (Arendt, ; Hoffman & Reiter, ; Srinivasan et al, ) have suggested that elevated melatonin levels during the prepubertal periods helps to maintain the hypothalamic–pituitary–gonadal axis in a state of quiescence, thus inhibiting the onset of pubertal development; while the reduction in melatonin levels that begin at the onset of puberty activates hypothalamic pulsatile secretion of gonadotropin‐releasing hormone resulting in the onset of puberty (Murcia García et al, ). In a few human studies, there have been reports that have associated precocious puberty with low melatonin levels (Commentz & Helmke, ; de Holanda et al, ), although clinical studies have yielded inconclusive and/or conflicting results (Srinivasan et al, ).…”
Section: Exogenous Melatonin Use and Sexual Maturation In Adolescentsmentioning
confidence: 99%